Figurative Language in Speechless Song by Naomi Scott : What Meaning Lies Behind It? - Tracy, Nafissa; Mustofa, Mutmainnah; Effendi, Erfan; Nadzifah, Wardatun (INTERACTION: Jurnal Pendidikan Bahasa, 2021)
Figurative language is one part of semantic study which is usually used in poems and song to enrich the meaning of that literary works. This research aimed to find out the kinds of figurative language, the most popular kinds of figurative language, and the meaning lies behind Speechless song lyrics by Naomi Scott. The method of this study used descriptive qualitative design. The source of the data in this research was the lyrics of Speechless song. However, the researchers collected the data by reading the lyrics. The results showed there were three kinds of figurative language used in that song such as: metaphor, hyperbole and personification. Metaphor was the most repeatedly utilized in the song with 53% use, hyperbole was 30% and personification 15%. The meaning lies behind this song tells about feminism or women empowerment. Therefore, all figurative languages used were aimed to convey the personal emotional power of the singer toward her oppressor. It was vividly expressed by Naomi Scott by using those figurative languages in her song lyrics.